Diabetes Caused by Statin Use: A Review - Zulfiana, Risa; Medina, Farah; Suharjono, Suharjono (Journal of Islamic Pharmacy, 2020)
Statins are generally recognised as being safe and well tolerated cholesterol-lowering drug and have been successfully used for prevention of primary and secondary cardiovascular disease. However, Some researchers have reported diabetes development in patients taking statins. A number of meta-analyses conducted in recent years have proved that the association is real even though its causality have not been fully elucidated. Various pathophysiological mechanisms that could explain the increased risk of diabetes in patients treated with statin have been described. These are mainly responsible for impairment of Î² -cell insulin secretion and alteration of intercellular signaling through depletion of important downstream products. Â This review aims to examine the relationship between statin treatment and the presence of diabetes. Previous clinical reviews of the evidence and pathophysiological mechanisms involved may also be explained. Furthermore, many studies have concluded that Pitavastatin and pravastatinom do not affect glycemic control and may be a beneficial treatment option in patients with, or at risk for, type 2 diabetes.